Prevalencia de la enfermedad de Newcastle en aves de traspatio mediante el uso de la prueba de Elisa indirecto para la detección poblacional en la provincia de Cotopaxi. - Vizuete Jaramillo, Katherine Pryscila (2022)
Newcastle disease (NDV) is one of viral conditions with pathogenesis high degree because it constitutes to a public health problem due to its zoonosis, it mainly affects low production, causing birds high mortality that acquire the disease. velogenic strain impacting to owners at productive and economic level. The objective of this research was to determine Newcastle prevalence on backyard birds, the same one that was developed in rural area of Cotopaxi province, specifically at parishes belonging to Latacunga and Salcedo cantons, which represent largest geographic area, with the purpose to determine NDV prevalence on backyard birds using indirect enzyme-linked immunosorbent assay (ELISA-i) for detection on bird population that present antibodies to disease at Cotopaxi province. 180 backyard birds were taken at random from rural parishes, taking into account age and sex variables, it tried to find out how many animals presented relatively positive titles to disease, for which it is proceeded to take blood samples from birds, obtained directly from brachial vein by direct puncture with a syringe and transported by red cap vacutainer tubes to laboratory extraction of blood serum. The used analysis was indirect ELISA technique, which consists sample processing through enzymatic reaction by staining for subsequent analysis through immune reaction to pathogen at light reflection on the plate, reflecting data referring in to the case if the bird is affected by disease. As results, it was found that according to sex variable, males denoted a positive percentage of 3.33%, while 10.55% was found in females. The origin factor showed a higher prevalence at 11 de November and Alaquez parishes belonging to Latacunga, as well as in Mulalillo parish from Salcedo canton with 4 positive cases, respectively. It was obtained through results of analysis on Newcastle prevalence in rural parishes of the province is 13.88%, which is relatively low considering last census carried out by AGROCALIDAD in 2015, which the province presents 18.02% of disease.